REPRESENTASI NILAI BUDAYA ACEH PADA FILM HIKAYAT TERAKHIR - Inayatillah, Inayatillah; Junaidi, Junaidi; Mariani, Mariani (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
Film is one of the effective and popular media in presenting the cultural values ​​and life of a region or nation. The film that is used as the object of this research is the film